Florence and the Medici : - Hale, J. R. (Thames and Hudson, 1977)
The enduring fascination of the Medici springs from their ability--as individuals and as a family--to control the government of Florence, first as a quasi-democracy and finally through inheritance. Based on the latest research, this perceptive study, by one of the finest Renaissance scholars of the day, reveals the causes and the nature of the Medicis' power of patronage from the early 15th-century through the early 18th